First record of phoresy by Parachernes setiger Mahnert, 1979 (Pseudoscorpiones, Chernetidae) on the fly Artemita amenides (Walker, 1849) (Diptera, Stratiomyidae, Pachygastrinae) in the Central Amazon - Guimarães, Cleiton R.; Sena, Jasmine D. N.; Tizo-Pedroso, Everton; Pujol-Luz, José R.; Rafael, José A. (Entomological Communications, 2025)
Pseudoscorpions can attach themselves to various mobile arthropods. This interaction is known as phoresy. We report for the first time the phoretic interaction between pseudoscorpion (Arachnida) and Stratiomyidae (Diptera) in the New World, as well as the first phoretic interaction involving Parachernes setiger Mahnert, 1979 (Pseudoscorpiones, Chernetidae), in this case with Artemita amenides (Walker, 1849). Three specimens were attached to the fly's mid tibia (1 specimen) and hind tibia (2 specimens on the same side).